2017
DOI: 10.1051/0004-6361/201629702
|View full text |Cite
|
Sign up to set email alerts
|

Coronal loop seismology using damping of standing kink oscillations by mode coupling

Abstract: (2017) Coronal loop seismology using damping of standing kink oscillations by mode coupling II. additional physical effects and Bayesian analysis. Astronomy and Astrophysics, 600 . A78. Permanent WRAP URL:http://wrap.warwick.ac.uk/85278 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 105 publications
8
101
0
Order By: Relevance
“…We follow the model comparison procedure based on Bayesian inference and Markov chain Monte Carlo (MCMC) sampling described in Pascoe et al (2017a) and applied to a coronal loop intensity profile in Pascoe et al (2017b).…”
Section: Bayesian Inferencementioning
confidence: 99%
See 3 more Smart Citations
“…We follow the model comparison procedure based on Bayesian inference and Markov chain Monte Carlo (MCMC) sampling described in Pascoe et al (2017a) and applied to a coronal loop intensity profile in Pascoe et al (2017b).…”
Section: Bayesian Inferencementioning
confidence: 99%
“…where the evidences, P pD|Mq are calculated as described in Pascoe et al (2017a). To define evidence thresholds the natural logarithm of this factor, i.e.…”
Section: Bayesian Inferencementioning
confidence: 99%
See 2 more Smart Citations
“…The seismological method proposed by Pascoe et al (2013a) was first used to calculate the transverse density profile of coronal loops by Pascoe et al (2016b), and further developed by Pascoe et al (2017a) to account for additional physical effects including a time-dependent loop length and the presence of the second and third parallel harmonics of the kink mode. The seismological estimate of the inhomogeneous layer width of Loop #3 in Pascoe et al (2017a) was found to be consistent with an independent estimate based on forward modelling of the transverse intensity profile (Pascoe et al 2017b), while a statistical study of 233 coronal loops found that 75% exhibit evidence for an inhomogeneous layer (Goddard et al 2017). …”
Section: Introductionmentioning
confidence: 99%